An intelligent trainee selection model - Mohamad Mohsin, Mohamad Farhan; Ahmad, Faudziah; Mohamed Din, Aniza; Ku-Mahamud, Ku Ruhana; Din, Roshidi (2011)
This paper proposed an intelligent model that is aimed at facilitating key workers select suitable trainees for a training program.The proposed model is initiated because it has been found that many motivational training programs fail to meet their objectives because there is a mismatch between the needs of training programs and the integrity levels of trainees.The proposed model consists of three modules namely personality characteristics identification, training program requirements identification, and trainee selection agent.A dataset for the study called Trainees Integrity Dataset (TID) is mined using association rule to discover important personality characteristics. TID is obtained from Langkawi District Education Office (LDEO) and it has 1500 respondents which represents secondary school teachers in Pulau Langkawi, Kedah, Malaysia who attended a training program organized by LDEO in 2009.The proposed model is intended to produce an efficient selection process and suitable trainees.